2014
DOI: 10.1016/j.febslet.2014.08.039
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1 acts as a barrier to pluripotent reprogramming by promoting neural progenitor fate commitment

Abstract: Edited by Ned Mantei Keywords:Induced pluripotent stem cell Induced neural stem/progenitor cell Cyclin D Cell cycle a b s t r a c t A short G1 phase is a characteristic feature of the cell cycle structure of pluripotent cells, and is reestablished during Yamanaka factor-mediated pluripotent reprogramming. How cell cycle control is adjusted to meet the requirements of pluripotent cell fate commitment during reprogramming is less well understood. Elevated levels of cyclin D1 were initially found to impair plurip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(65 citation statements)
references
References 30 publications
0
64
1
Order By: Relevance
“…Nevertheless, Cyclin Ds have a tissue-specific expression during gastrulation (Wianny et al 1998) that resembles the pattern observed during differentiation of hESCs in vitro, suggesting that their role in the mechanisms controlling early cell fate decisions could be conserved in vivo. Cyclin D activity also promotes neuroectoderm formation during induced pluripotent stem cell generation through up-regulating Pax6 (Chen et al 2014), and, importantly, Cyclin D maintains the self-renewal of a broad number of adult stem cells, including mammary stem and progenitor cells (Jeselsohn et al 2010), neuronal stem cells (Roccio et al 2013), and hematopoietic stem cells (Lange and Calegari 2010). Therefore, the basic mechanisms uncovered by these studies could also be relevant for adult stem cells and represent an important step toward understanding the balance between differentiation and self-renewal during organ development and repair.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, Cyclin Ds have a tissue-specific expression during gastrulation (Wianny et al 1998) that resembles the pattern observed during differentiation of hESCs in vitro, suggesting that their role in the mechanisms controlling early cell fate decisions could be conserved in vivo. Cyclin D activity also promotes neuroectoderm formation during induced pluripotent stem cell generation through up-regulating Pax6 (Chen et al 2014), and, importantly, Cyclin D maintains the self-renewal of a broad number of adult stem cells, including mammary stem and progenitor cells (Jeselsohn et al 2010), neuronal stem cells (Roccio et al 2013), and hematopoietic stem cells (Lange and Calegari 2010). Therefore, the basic mechanisms uncovered by these studies could also be relevant for adult stem cells and represent an important step toward understanding the balance between differentiation and self-renewal during organ development and repair.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Pauklin et al reported that in late G1, cyclin D1 is induced and forms a complex with locus-specific transcription factors to recruit transcriptional coactivators onto neuroectoderm genes and corepressors onto endoderm genes in stem cells [52]. Importantly, it has been shown that the activities of D-type cyclins also promote neuroectoderm formation during hiPSCs generation through up-regulating Pax6 [53]. Thus, we can speculate that D-type cyclins may also influence phenotype-associated gene expression in NP.…”
Section: Discussionmentioning
confidence: 99%
“…Human Abcg2 was amplified by PCR with specific primers (forward: 5′‐ACTCTCCAGATGTCTTCCAG‐3′; reversed: 5′‐TGTGAGGATAAATCATACTG‐3′) and cloned into the Nhe I and Eco RI cutting sites of lentiviral expression vector, pLKO.1‐EF1‐IRES‐m Cherry to generate pLKO.1‐EF1‐h Abcg2 ‐IRES‐mCherry expression constructs.…”
Section: Methodsmentioning
confidence: 99%